Estudo comparativo dos cristais L-alanina, L-treonina e taurina com variação de temperaturas por espectroscopia Raman - CAVAIGNAC, André Luís de Oliveira (2015)
Structural, magnetic and magnetocaloric properties of the RMn2Si2 compounds (R = Tm, Dy and Tb) were studied. X ray diffraction analysis and structure Rietveld refinement shows that the samples crystallize with the desired tetragonal I4/mmm structural phase. Magnetization measurements shows second order magnetic phase transition from paramagnetic (PM) to ferromagnetic (FM) state for TmMn2Si2 compound around T = 5.2 K. On the other hand, DyMn2Si2 and TbMn2Si2 compounds present multiple phase transitions below 100 K. DyMn2Si2 present four magnetic phase transitions while TbMn2Si2 present two magnetic phase transition. Both compounds present first order FM phase transitions originated from ordering of rare earth sub-lattice. In addition, DSC measurements indicated that DyMn2Si2 and TbMn2Si2 compounds present high temperature phase transition at T~ 425 K and 444 K associated to the AFM coupling in the Mn sub-lattice. Magnetic hysteresis loop was used to characterize exchange bias effect in the DyMn2Si2 observed for magnetic fields higher than 35 kOe in which was associated to interactions between AFM and FM magnetic domain present in this compound. The largest magnetocaloric effect (MCE) was observed for TmMn2Si2 compound, when compared with other studied compound. The maximum values of entropy variation change −∆𝑆𝑀 𝑚á𝑥 and the Relative Cooling Power (RCP) found for TmMn2Si2 were, respectively, 18.5 J/kg.K and 247.5 J/kg for a magnetic field change (H) of 50 kOe. Significant values of −∆𝑆𝑀 𝑚á𝑥 (~8.2 J/kg.K and ~9.7 J/kg.K@50 kOe, respectively) and RCP (124.6 J/kg and 233 J/kg@50 kOe, respectively) as well as successive magnetic phase transitions were observed for DyMn2Si2 and TbMn2Si2 compounds. Also these two compound exhibits a table like EMC presenting a wide working window for practical applications. The results obtained for compounds motivate the preparation of a composite sample with the following concentrations 10% de TmMn2Si2, 15% de HoCoSi, 35% de DyMn2Si2 e 40% de TbMn2Si2, aiming further increase in the temperature range of maximum EMC. The maximum entropy change variation obtained for the composite sample was ~4.6 J/kg.K over a temperature range of ~80𝐾. Our results show that the compounds RMn2Si2 present important characteristics for application in magnetic refrigeration for cryogenic temperatures. Besides, it is possible to get a larger working region, when these compounds are associated forming a composite material.